2019
DOI: 10.1108/ijem-03-2018-0102
|View full text |Cite
|
Sign up to set email alerts
|

Exploring school principals’ personal identities in Cyprus from a values perspective

Abstract: Purpose The purpose of this paper is to explore a broader understanding of the role of Cypriot school principals’ personal identities, through a values system perspective, when exercising their leadership. Design/methodology/approach A multicase study methodology was followed with five school principals, representing five different leadership styles. In each case, an in-depth investigation of the school principal’s personal identity was undertaken. School principals’ personal values were explored during inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Gold, 2004; Baig, 2010; Notman, 2017; Crow and Møller, 2017). In addition, in relation with the context of Cyprus, recent studies on school principalship (Kafa and Pashiardis, 2019, 2020) revealed that school principals promoted a number of values such as that of kindness and commitment in order to build relationships and contacts with various external stakeholders such as parents, as well as to maintain good relations with teachers within their schools. In general, in the European context it seems that successful school principals create a vision, which is values-driven and can be shared with all stakeholders (Pashiardis et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Gold, 2004; Baig, 2010; Notman, 2017; Crow and Møller, 2017). In addition, in relation with the context of Cyprus, recent studies on school principalship (Kafa and Pashiardis, 2019, 2020) revealed that school principals promoted a number of values such as that of kindness and commitment in order to build relationships and contacts with various external stakeholders such as parents, as well as to maintain good relations with teachers within their schools. In general, in the European context it seems that successful school principals create a vision, which is values-driven and can be shared with all stakeholders (Pashiardis et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Contexts highlighted include geographic, historical and generational, and gender and how gender intersects with race in powerful and paradoxical ways and how professional identities shift over time and respond to school-wide change and interact on social media (Johnson and Crow, 2017). Other studies have emphasized the importance of values connected to the principals' understanding of their position and role and the improvement of the welfare of the people with whom principals were in frequent personal contact (Kafa and Pahiardis, 2019).…”
Section: Strand 3: Successful Principalship As Socially Constructedmentioning
confidence: 99%
“…School leadership is under increasing scrutiny as it could contribute to student attainment and school improvement in the recent decade. Literature provides evidence that school leadership has a significant impact on student learning (Adams, 2018; Hallinger & Kulophas, 2020; Kafa & Pashiardis, 2019; Krüger et al, 2007; Leithwood et al, 2008). However, the role of schools has been dramatically modified over decades due to the demand of education reform (Bush & Ng, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of schools has been dramatically modified over decades due to the demand of education reform (Bush & Ng, 2019). Schools have become more complex organizations and thus there is a need to focus on school leaders’ values in enhancing effective leadership (Kafa & Pashiardis, 2019). In relation to this concern, effective leadership is underpinned by the school leaders’ personal values: their qualities, beliefs, and behavior, which serve as the sources of variation in leadership practices (Hallinger, 2011).…”
Section: Introductionmentioning
confidence: 99%